Outer membrane vesicles of bacteria - Chatterjee, S.N (SpringerBriefs in Microbiology, 2012)
This book provides a detailed account of the physico-chemical properties and biological functions of the outer membrane vesicles (OMVs) of different pathogenic and non-pathogenic Gram-negative bacteria. It also includes an authentic record of the first systematic study that discovered the mechanism of OMV formation by a pathogen, Vibrio cholerae, and proposed that the process represented a novel secretory activity of bacteria. Furthermore, the authors present clinical and laboratory data on the use of OMVs as immunogens, as effective and licensed vaccines against Neisseria meningitidis serogroup B infections and on the development of more effective vaccines against other human and animal pathogens including Vibrio cholerae. This volume thus bears witness to the emerging revolution in the field of vaccines against pathogens and closes with a discussion of open questions and future research on OMVs.